The Awakening Chinese Economy: Macro and Terms of Trade Impacts on 10 Major Asia-Pacific Countries - Yin Hua Mai; Philip Adams; Peter Dixon; Jayant Menon (Asian Development Bank (ADB), 2010)
This paper analyzes the impact that terms of trade (TOT) are likely to have on the growth of the People's Republic of China's (PRC) neighboring countries. Two scenarios employing a dynamic computable general equilibrium framework are considered: (i) a convergence scenario, where historical trends are projected; and (ii) a baseline scenario, where technological progress in the PRC is placed in line with that of the United States (US). The results show that the PRC's technological convergence leads to increased world prices for mining products, and lower world prices for manufactures, especially those exported extensively by the PRC. On the whole, however, the effects on the growth and TOT of the PRC's neighboring countries are relatively small. The modelling framework used in this study explicitly captures the various offsetting effects that dampen the impact on TOT and contribute to the small impact on growth. In addition, the additional capital required to finance the PRC's growth comes predominantly from domestic savings, placing little pressure on the global supply of capital. Thus, an awakening PRC is unlikely to make a dramatic entrance despite the country's overall positive impact on the region – although there is nothing to fear, there is also only little to gain.
hdl:11540/1938
Keywords: C68; F17; F47; 330; computable general equilibrium; multicountry models; People's Republic of China; terms of trade